Biomonitoring of airborne metals using the Lichen Xanthoria parietina in Kocaeli Province, Turkey - ÇOBANOĞLU, GÜLŞAH (ELSEVIER SCIENCE BV, 2012)
Airborne metal deposition in the major urban and the industrial districts of Kocaeli was monitored using Xanthoria parietina lichen specimen as a biomonitoring organism. Lichen samples were analyzed for Al, As, Co, Cd, Cu, Fe, lig, Mn, Ni, Pb, Ti, TI, V and Zn contents to determine the relationship between the potential pollutant sources in the region and the degree of airborne metal deposition. Results showed that airborne metal deposition in the Kocaeli province was widespread and environmental alteration was serious near the industrial facilities. Mean metal concentrations of lichen samples in the industrial district (Dilovast) of Kocaeli were two to seven folds higher than those in the urban districts of Kocaeli: Mn (7), Pb-Cd-Zn (6), Fe-Ni-Cu (3) and Al-Co-Ti-Hg-As-V (2). Environmental alteration in Dilovasi region was severe in terms of all metals analyzed. Cluster analysis showed that metal industry (iron-steel, aluminum, zinc) in Dilovasi, fossil fuel combustion processes related to the industry and power plant and heavy traffic contributed significantly to the metal emission in Dilovasi region. Airborne metal deposition in the urban districts of Kocaeli was high especially around the coal-fired cement plant in Hereke and petroleum refinery in Korfez. Fossil fuel combustion and traffic emission were among the important sources of airborne metals in the urban-suburban districts. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Heavy metal; Air pollution; Epiphytic lichen; Biomonitoring; TRACE-ELEMENT CONTAMINATION; AIR-QUALITY ASSESSMENT; HEAVY-METALS; POLLUTION; TUSCANY; THALLIUM; HEALTH